Targeting the IGF-Axis in Cultured Pediatric High-Grade Glioma Cells Inhibits Cell Cycle Progression and Survival - Yinhsuan Michely Chen; Matthew Leibovitch; Michele Zeinieh; Nada Jabado; Pnina Brodt (MDPI AG, 2023)
Pediatric high-grade gliomas (pHGG) accounts for approximately 8-12% of primary brain tumors in children. Prognosis is poor, with a median survival of 9-15 months. Insulin-like growth factor 1-receptor (IGF-1R) gene amplifications have been identified in high-grade gliomas and may contribute to its highly aggressive phenotype, but the effect of IGF inhibitors on pHGG is yet to be determined. In the present study, we analyzed the response of patient-derived pediatric high-grade glioma cells to a novel IGF-1R inhibitor, the IGF-Trap. Using immunohistochemistry, we found that IGF-1R was localized to both the nucleus and cell membrane in different pHGG patient-derived xenograft (PDX) lines under basal conditions. In response to ligand binding, nuclear levels of the receptor increased, and this was associated with the transcriptional upregulation of both the receptor and cyclin D1, suggesting that IGF-1R could regulate its own expression and cell cycle progression in these cells. Insulin-like growth factor-1 (IGF-1) increased the proliferation of the pHGG cells DIPG13 and SGJ2, and this could be blocked by the addition of the IGF-Trap. The IGF-Trap reduced the colony formation of these cells in an optimal growth medium and impeded the ability of IGF-1 to rescue DIPG13 cells from starvation-induced apoptosis. Collectively, these results implicate the IGF-1 axis in the regulation of cell cycle progression, cellular proliferation, and cell survival in pHGG, and identify the IGF-axis as a target and the IGF-Trap as a potential inhibitor of this axis in pHGG.